British Medical Journal. Supplement : A general medical service for the nation ([London : British Medical Association])
1938-04-30 1938 1930s 14 pages 264 APRIL 30, 1938 REPORT OF COUNCIL SUPPLEMENT TO THE BRITISH MEDICAL JOURNAL to affect adversely the intimate relationship between doctor and patient, which, although difficult to define, is a factor of essential importance in the successful treatment of the patient. A system that does not provide for free and open choice, however excellent it may be from other points of view, suffers a serious handicap for which no administrative excellence can compensate. (c) Continuity of treatment is necessary if medical treatment is to have its maximum effect. At its worst the present system means that a person who experiences prolonged unemployment will at a certain stage pass from the care of the practitioner of his choice to that of the district medical officer; on returning to work he will return to the practitioner of his choice. (d) It is in the interests of the public that the general practitioner should maintain a high standard of efficiency. General practitioners as a body cannot maintain this standard of work, for which they are fully equipped by their training, if opportunities for greater experience are removed and concentrated in the hands of a selected few. (e) The local authority and general practice are two important agencies in securing and maintaining the health of the community they serve. There should be co-operation and collaboration between them — that is, between the public health authority and the general practitioners of the area. The existing machinery of private practice should be used as far as possible for discharging the functions of the local authority in health matters. The "free choice" method of providing public assistance domiciliary medical services offers an effective means of contact of a kind advantageous to the authority, the profession, and the public. 97. The experience which is being gained in the urban and rural areas where the free or open choice method has been adopted has shown that this system means a new and better atmosphere, medical work more freely accepted and well done, and a workable administrative machine. (d) Existing Public Health Services 98. Environmental Services. — The adoption of the Association's proposals for a general medical service for the nation would in no way diminish the need for the maintenance and development of the environmental and impersonal protective services such as those directed to sanitation. pure water and food supply, good housing, and the control of infectious disease. In England and Wales there are one-third of a million dwellings which, according to official standards, are overcrowded, while in the urban areas of Scotland conditions are worse. There are over 2,000 different bodies, statutory and non-statutory, which are supplying water to the community, and as yet few steps have been taken in the direction of planning the nation's water resources. Little has been done to deal with the evil of atmospheric pollution by smoke. The noise of our towns increases, and there is practically no attempt by statutory bodies to abate this evil. Water-borne and milk-borne epidemics still occur, and too little attention is paid to the safety of such an important food as milk. The problems of nutrition and physical education are just beginning to receive the official attention which they deserve. 99. Personal Health Service. — It is believed that the adoption of the proposals set out in this document will add greatly to the national health. But they cannot and will not yield their greatest value until greater attention is paid to the economic, social, and environmental factors upon which a healthy life depends. Their adoption would, however, involve a re-examination of the existing health provision for individuals. Such specialist services as those dealing with tuberculosis and venereal disease should continue much in their present form; such services as those provided for mothers and infants and for school children will need substantial modification if overlapping with the general medical service is to be avoided. 100. Reference has already been made to the proposals for a national maternity service. The utilization of the services of the general practitioner for the ante-natal, natal,and post-natal care of the normal mother would render unnecessary the large number of ante-natal and post-natal clinics which have in late years been established by local authorities. When there are available to the mother in her home the services of a midwife, a general practitioner, an obstetric specialist, and the necessary auxiliary facilities, the need for institutional accommodation for normal cases will be greatly lessened. On the other hand, the need for consultant and specialist facilities in the home and in the clinic or out-patient department, and for institutional accommodation for difficult cases, will be increased rather than diminished. 101. The provision of a family doctor for every family would secure for infants and young children the service which the general practitioner is capable of rendering. While this would render unnecessary any other provision for their general medical care, the system of child welfare centres at which mothers can obtain advice and guidance in the care and nurture of their children would continue to be of the greatest value. Instruction in mothercraft and the general care and hygiene of infants, hints on nursing, dressing, and bathing, and regular weighing are of the greatest possible value and can be most efficiently undertaken in infant welfare centres. The centres should continue their educational and social work in collaboration with the family doctor. The provision of a family doctor for every child would enable the clinics to increase the value of their work by concentrating on the more positive aspects of health. They should be utilized to a greater extent for investigation into the origin and early manifestations of disease. 102. One of the most valuable developments in our educational system during the past generation has been the medical inspection of school children and the provision made for securing the treatment of the defects discovered on inspection. The work of regular medical inspection, particularly of those children found to be suffering from serious or persistent defects, should of course continue and develop. It would not, however, be necessary to provide treatment facilities for those conditions normally treated by the family doctor. Through his agency the necessary specialist facilities would be available, and the treatment facilities given by the school medical service should be limited to those conditions which can be more effectively dealt with in the clinic or the hospital outpatient department. As a result the school medical doctor, like the infant welfare doctor, would be enabled to concentrate his attention on a field of great potentiality, that of the positive prosecution of mental and physical health. (e) Some Special Services 103. Industrial Medical Services. — The development of industry with the related increase in industrial hazards led in 1898 to the appointment by the Home Office of a Medical Inspector of Factories. There are now eight such medical inspectors and one Medical Inspector of Mines, while closely related to the work of the former there are some 1,700 examining surgeons. The Association realizes that the work of these practitioners is an essential part of our public health service, more valuable perhaps because of the part-time nature of the examining surgeons' duty which allows of a fusion between general practice and industrial hygiene. In addition there has grown up of late a practice by which the larger industrial concerns appoint medical officers on a whole-time or part-time basis to supervise the health of industrial workers and the hygiene of industrial plants. 104. The Association realizes the valuable nature of this work. Recognizing, in close co-operation and agreement with representatives of these industrial medical officers, that such a service could not wisely be allowed to develop out of contact with general practice, it has drawn up an ethical code within which it is believed this new health service will develop as part of the medical services of the nation, in harmony and co-operation not only with 292/847/1/60